Measurement of non-isothermal oxygen potentials in a Cu–Fe–Ca–S–O liquid during reduction of chalcopyrite in lime and carbon mixtures. (March 2014) - Jha, Animesh; Srikanth, S.
<x content-type="archive" xml:space="preserve">Abstract</x> The reduction of Indian chalcopyrite concentrates from the Ghatshila mines with carbon was studied in the presence of lime in the temperature range of 1123–1573 K. An attempt was made to determine the oxygen potential corresponding to the selective separation of two metals, copper and iron, during the reduction of chalcopyrite by carrying out electro-motive force (emf) measurements under isochronal heating rate conditions using an yttria-stabilised zirconia solid electrolyte cell with Cu/Cu2O as the reference electrode. The isochronal rate data for oxygen potential measurements were analysed by comparing them with the data from isothermal kinetics studies on the reduction of natural and synthetic chalcopyrite minerals in the above temperature range. The analyses of phases formed were carried out using the X-ray powder diffraction and scanning electron microscopic techniques, which showed the presence of a new quinary solid solution CIII phase. The solid solution phase CIII [Cu2S-CII(FeS⋅CaO)] forms as a result of mixing between the two rhombohedral lattices: high-temperature form of Cu2S and CII (FeO⋅CaS) compounds. The mechanism of reduction of chalcopyrite with carbon in the presence of lime is illustrated by the explanation of the role of the intermediate phases, CII, CIII and matte phases.